KARAKTERISTIK DAN PERSEPSI WISATAWAN TERHADAP DAYA TARIK WISATA PANTAI KATA DI KOTA PARIAMAN, SUMATERA BARAT - Lucky Setiawan; Ida Ayu Suryasih (JURNAL DESTINASI PARIWISATA, 2016)
Abstract Kata Beach as a tourist attraction has the potential and uniqueness of the coastal tourist attraction in general. But with the potential and uniqueness of the tourist attraction that should Kata Beach can attract more tourists, because at this time the number of tourists visiting the tourist attraction Kata still little and visited only at certain times such as the feast of Eid al-Fitr and the day-to-day national holiday. Local people who trade or sell around Kata Beach tourist attraction has yet to obtain maximum profit. This is caused by the time they trade and sell uncertain because they only sell at the moment busy travelers, if not crowded tourists who visit them do not open a shop to sell. Obviously this becomes a problem for the manager of a tourist attraction Kata Beach. To overcome these problems the need for improvements made ??by the manager of a tourist attraction Kata, by way of knowing in advance how the characteristics of tourists visiting Kata Beach, as well as knowing how travelers perception of the condition of Kata Beach is a tourist attraction at this point. So from the data manager can analyze the intended target market and to facilitate the development of decision-making will be done. Collecting data in this study through observation, interviews, questionnaires, and Documentation studies. The type of data being used is supported by quantitative data and qualitative data. While the data sources used in the form of primary data and secondary data. Analysis using descriptive statistics which describe or illustrate the data that has been collected from a population, which is obtained by Likert Scale Data measurement techniques. Characteristics of tourists visiting the tourist attraction Kata very good variety of indicators of gender, age, education, occupation and region of origin. While the perception of tourists on Kata Beach scored poorly on 6 indicators of security, number of toilets, cleanliness of restrooms, parking lot security, parking attendants skills and number of security officers. So it is necessary to reform by the manager for the indicators that scored poorly perceived by the tourists who visit.